A study on traditional beliefs and practices in newborn care among mothers in a tertiary health care centre in Vijayapura, North Karnataka - N., Nethra; Udgiri, Rekha (International Journal Of Community Medicine And Public Health, 2018)
Background: Culture is defined as a shared system of beliefs, values and behavioral expectations that provide social structure for daily living. Not all customs and beliefs are harmful. Some of them have positive values while others may be of no role or positively harmful for neonate’s health in various forms like physical, psychological, social development. The objective of the study was to explore the traditional beliefs and practices in new born care. Methods: A cross sectional study was conducted at post-natal ward of BLDEU’s Shri B M Patil Medical College, Hospital and Research Centre, Vijayapura from June 2015 to July 2015. A total of 200 mothers were interviewed and data was collected after obtaining the consent. Results: In the present study, majority of the mothers were in age group between 19-22 years (45%). 16% of the mothers discarded the colostrum believing it is harmful. Application of kajal to the newborn’s face and eyes will be practiced among 88%. 75% of the mothers practiced pouring oil into the ears. Conclusions: Findings of our study highlights some of the good practices in the newborn care which can be motivated, at the same time the harmful practices can be avoided by educating and counselling the mother and her family members.